Economic evaluation of enhanced asthma management: a systematic review - Yong YV; Shafie AA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2014)
Objectives: To evaluate and compare full economic evaluation studies on the cost-effectiveness of enhanced asthma management (either as an adjunct to usual care or alone) vs. usual care alone. Methods: Online databases were searched for published journal articles in English language from year 1990 to 2012, using the search terms '"asthma" AND ("intervene" OR "manage") AND ("pharmacoeconomics" OR "economic evaluation" OR "cost effectiveness" OR "cost benefit" OR "cost utility")'. Hand search was done for local publishing. Only studies with full economic evaluation on enhanced management were included (cost consequences (CC), cost effectiveness (CE), cost benefit (CB), or cost utility (CU) analysis). Data were extracted and assessed for the quality of its economic evaluation design and evidence sources. Results: A total of 49 studies were included. There were 3 types of intervention for enhanced asthma management: education, environmental control, and self-management. The most cost-effective enhanced management was a mixture of education and self-management by an integrated team of healthcare and allied healthcare professionals. In general, the studies had a fair quality of economic evaluation with a mean QHES score of 73.7 (SD=9.7), and had good quality of evidence sources. Conclusion: Despite the overall fair quality of economic evaluations but good quality of evidence sources for all data components, this review showed that the delivered enhanced asthma managements, whether as single or mixed modes, were overall effective and cost-reducing. Whilst the availability and accessibility are an equally important factor to consider, the sustainability of the cost-effective management has to be further investigated using a longer time horizon especially for chronic diseases such as asthma.